Conservative management of Thrombosed external hemorrhoid - Kadem, Muslim Kandel (University of Thi-Qar Journal of Science, 2013)
A prospective study of 20 patients (12 males ,8 female) with main age about 47 years in both sexes all were complained from thrombosed external hemorrhoid (TEH) was conducted, most of them complained from at least one symptom discharge , pain , lump….As we know the surgical management is the gold standard management of such conditions , but in this study .( because some patients refuse operation either afraid from operation or shying specially women in our society ) so try conservative management No surgery, no baths , but treated with gentle dry cleaning with smooth toilet paper after defecation, with intravenous antibiotics (cefetriaxazon, metronidazol) for 2 weeks then Follow-up information was collected six months after admission the results are :- 6 Pt (30%) (described as “healed” without need operation) , 10 Pt (50)% (described as unchanged with minimal symptom no need another operation), 4pt (20%) become sever pain or abscess formation need urgent operation.Only 2pt out of 16 (12.5%) have recurrence. In spit of the surgery is the gold standard therapy for TEH butwe can use conservative management especially for patients who were unfit for surgery or who refused with minimal risks.